Is there A Role for Alpha-Linolenic Acid in the Fetal Programming of Health? - Leikin-Frenkel, Alicia I. (J Clin Med, 2016)
The role of ω3 alpha linolenic acid (ALA) in the maternal diet during pregnancy and lactation, and its effect on the prevention of disease and programming of health in offspring, is largely unknown. Compared to ALA, ω3 docosahexaenoic (DHA) and eicosapentaenoic (EPA) acids have been more widely researched due to their direct implication in fetal neural development. In this literature search we found that ALA, the essential ω3 fatty acid and metabolic precursor of DHA and EPA has been, paradoxically, almost unexplored. In light of new and evolving findings, this review proposes that ALA may have an intrinsic role, beyond the role as metabolic parent of DHA and EPA, during fetal development as a regulator of gene programming for the prevention of metabolic disease and promotion of health in offspring.